Technique and Quality Translation of Idhafi Phrases in The Poetry of Asyhadu An La Imraata Illa Anti by Nizar Qabbani - Lalu Muhammad Faesal Asy’ari; Yoyo Yoyo (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2021)
The translation process is an activity of transferring one language to another, from the translation process the researcher examines the translation techniques and translation quality of the collection of translation poems by Nizar Qabbani entitled Asyhadu An La Imraata Illa Anti. The methodological foundation that the researcher uses is a qualitative method. In this study, the researcher found 160 Idhafi phrases which were translated using 15 translation techniques, and 2 translation techniques that had good quality in conveying the intent, message, and purpose to the reader into the target language. That is, the equivalent technique generally has the highest value on three aspects of assessment for the quality of translation, among others, the accuracy aspect has a score of 83.3%, then the acceptability aspect has a score of 85.7%, and in the readability aspect, it has a score of 78.6% for further research. The researcher can discuss in more detail the translation method of Nizar Qabbani's Poetry.